Exploring the Antioxidant Features of Polyphenols by Spectroscopic and Electrochemical Methods - Berta Alcalde; Mercè Granados; Javier Saurina (MDPI AG, 2019)
This paper evaluates the antioxidant ability of polyphenols as a function of their chemical structures. Several common food indexes including Folin-Ciocalteau (FC), ferric reducing antioxidant power (FRAP) and trolox equivalent antioxidant capacity (TEAC) assays were applied to selected polyphenols that differ in the number and position of hydroxyl groups. Voltammetric assays with screen-printed carbon electrodes were also recorded in the range of −0.2 to 0.9 V (vs. Ag/AgCl reference electrode) to investigate the oxidation behavior of these substances. Poor correlations among assays were obtained, meaning that the behavior of each compound varies in response to the different methods. However, we undertook a comprehensive study based on principal component analysis that evidenced clear patterns relating the structures of several compounds and their antioxidant activities.